Invasive and chronic fungal lung infections - Periselneris, Jimstan; Armstrong-James, Darius (Annals of Research Hospitals, 2017)
Fungi are increasingly recognized as a cause of respiratory infection, particularly affecting individuals with either immune deficiency or localised lung destruction. The normal human host response effectively controls airborne fungi, but specific polymorphisms are associated with increased risk of developing fungal lung infection. Invasive fungal disease (IFD) is associated with neutropenia and haematological stem cell transplants. They are difficult to diagnose with certainty though the use of cross-sectional imaging and biomarkers has allowed targeted patient treatment. Mortality rates, though improving with antifungal therapy, remain unacceptably high. Chronic pulmonary fungal disease is associated with chronic respiratory disorders and is also difficult to diagnose with certainty. Treatment is chronic and often poorly tolerated, and even when successful unable to reverse existing lung damage. Further research is required to improve both diagnostics and therapy to improve outcomes in these infectious diseases.